Icon of the Transfiguration from Solovki Monastery: a Newly Discovered Masterpiece of the Novgorodian Icon Painting of the 16th Century - Buzykina, Iuliia N. (Actual Problems of Theory and History of Art, 2014)
The icon depicting the Transfiguration of Christ from the catholicon of Solovki Transfiguration monastery belongs to the most outstanding works of the Russian icon art of the 16th c., created by the best artists for the educated ecclesiastics. As this article is the first publication of the icon, which was only noted in literature before, we examined the written sources mentioning the icon, as well as its iconography and style in order to set its dating and the regional school of the icon painting to which the artist belonged. The written sources (inventories of Solovki monastery of the 16‒20th cc.) and stylistic features of the icon make it possible to say that the icon was painted between 1538 and 1549. The iconographic program of the icon, including two scenes besides the “Transfiguration” itself, which are “Parable of new wine in old wineskins” and “Healing of an epileptic” is unique. “Healing of an epileptic” is known in Byzantine and post-Byzantine art, however the only example of combining this miracle with the Transfiguration is the altar picture painted by Raphael in 1516–1520 for Giulio de Medici. The question of whether it is a coincidence remains open. The unique and sophisticated ascetic program makes it possible to suppose that donator of this icon was Philipp Kolychev. As a result, we can argue that the icon of Transfiguration was painted for the Solovki abbot Philipp Kolychev between 1538 and 1549 by a Novgorodian icon painter.
Keywords: Old Russian art; medieval art; art of the 16th century; icon painting; Russian icon; Philipp Kolychev; Solovki; Russian monasteries; iconography; healing of epileptic; parable of mew wine in old wineskins; Transfiguration; iconostasis